Kneeling for Justice: A Study on How the 30th Anniversary of the Nike "Just Do It" Campaign Starring Colin Kaepernick Was Portrayed by the Media - Leduc, Jayson (Université d'Ottawa / University of Ottawa, 2022)
In 2018 Nike collaborated with controversial NFL quarterback Colin Kaepernick on their 30th anniversary of their "Just Do It" campaign. Released on multiple platforms, the "Dream Crazy" campaign as it was labeled featured Kaepernick as well as other prominent athletes that broke all odds to become some of the biggest athletes in their sport. A prominent figure in the fight against racial injustice, Kaepernick triggered outrage when he started kneeling during the playing of the national anthem of the United States of America. Drawing from theories of Corporate Social Responsibility and Cause-Related Marketing, this thesis analyses media coverage of the "Dream Crazy" marketing campaign to understand why Nike would collaborate with Kaepernick. Employing qualitative thematic analysis, this thesis examined newspaper articles published around the release of the campaign. Research findings show that Nike received positive coverage as well as over forty-three million dollars in free media exposure. While some individuals burned their apparel in protest, Nike saw sales increase as consumers sought to demonstrate their support for Kaepernick and racial justice. Simultaneously, the campaign made the fight for racial justice a front-page topic as well as exposing Kaepernick's own struggle with being blackballed by the NFL for his public protests.
Keywords: Nike; Colin Kaepernick; Cause-Related Marketing; Corporate Social Responsibility; BLM; CRM